The Role of Technology in Improving the Effectiveness of Employee Recruitment and Selection - Dimas Bagus Susanto; Said Hamzali (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This research explores the role of technology in improving the effectiveness of employee recruitment and selection. Against the background of the importance of an effective recruitment and selection process for organizational performance, this research focuses on identifying the latest technologies that can optimize the process and evaluating their impact on speed, cost, and accuracy in employee selection. A qualitative approach with a literature study method was used to extract information from various relevant sources. The results show that the use of technologies such as applicant tracking systems (ATS), artificial intelligence (AI), and digital platforms can increase candidate reach, reduce recruitment time and costs, and improve accuracy and candidate experience. However, challenges such as start-up costs, training needs, and resistance to change were also identified. This research provides practical recommendations for organizations looking to adopt technology in employee recruitment and selection to achieve operational efficiency and competitive advantage.